Educational Values Contained in Sinrilik Pakeso-Keso Performance Makassar - Predi Wijaya, Eksar; Takwa, Takwa; Jum’atul Taqfiah, Suci (GERAM, 2024)
This research was motivated by the desire to explore the content of educational values in Pakeso-Keso Makassar Sinrilik performances. The main problem in this research is How is the Educational Value Contained in Pakeso-Keso Makassar Sinrilik Art Performance? This research aims to explore the educational values contained in the performance art. This research is descriptive qualitative in nature that utilises primary and secondary data. Primary data, obtained directly in the field through observation, interviews, and documentation. While secondary data, obtained from the main source in the form of Sinrilikna I Makdi Daeng Ri Makka manuscript text, and other related literature.  The results showed that there are five educational values contained in the Pakeso-Keso Makassar Sinrilik performance, namely moral, social, cultural, religious, and patriotism values. These findings provide insight into the richness of culture and educational values, especially in Makassar's traditional performing arts. In addition, the results of this study can be useful for the preservation and appreciation of the cultural heritage of ethnic groups in Indonesia.